3D reflection seismic imaging for open-pit mine planning and deep exploration in the Kevitsa Ni-Cu-PGE deposit, northern Finland - Malehmir, A.; Juhlin, C.; Wijns, C.; Urosevic, Milovan; Valasti, P.; Koivisto, E. (Society of Exploration Geophysics, 2012)
A 3D reflection seismic survey was conducted over an area of about 9 km2 at the Kevitsa Ni-Cu-PGE (platinum group elements) orebody, northern Finland, where open-pit mining started in mid-2012. The principal objective of the survey was to image major fault and fracture zones at depth that may have an impact on the mine stability and safety. Mine planning would then take into account the geometry of these zones at Kevitsa. Processing results, using conventional prestack DMO and poststack migration methods, show gently dipping and steeply dipping reflections from depths of approximately 2 km to as shallow as 150–200 m. Many of the reflections are interpreted to originate from either fault systems or internal magmatic layering within the Kevitsa main intrusion. Further correlation between the surface seismic data and VSP data suggests that numerous faults are present in the imaged volume based upon time shifts or phase changes along horizontal to gently dipping reflections. Some of these faults cross the planned open-pit mine at depths of about 300–500 m, and are therefore critical for geotechnical planning. In terms of in-pit and near-mine exploration, the magmatic layering internal to the intrusion controls the distribution of the bulk of economic mineralization. The ability to image this magmatic layering could therefore guide future drilling, particularly by constraining the presumed lateral extents of the resource area. Exploration also will target discrete reflectors that potentially represent higher-grade sulfide mineralization.